POTENTIAL OF ENDOPHY BACTERIAL ISOLATE FROM LEAF OF CHINESE TEMPERATURE (Cassia alata L) ON THE GROWTH OF THE BACTERIA OF STAPHYLOCOCCUS AUREUS - Enisa Kobandaha; Syam s kumaji; Adnan Malaha (LPPM Universitas Bina Mandiri Gorontalo, 2022)
ABSTRACT This research aims to To determine the effect of endophytic bacterial isolates from the leaves of the Chinese Ketepeng plant (Cassia Alata L) on the growth of Staphylococcus aureus and to determine the significant difference between each treatment of endophytic bacterial isolates from the leaves of the Ketepeng Cina (Cassia Alata L) plant against Staphylococcus aureus. This research method used a completely randomized design (CRD) with 4 treatments and 6 replications. The treatments were: BEKC 1 (Chinese Ketepeng Endophytic Bacteria 1), BEKC 2 (Chinese Ketepeng Endophytic Bacteria 2), Positive Control (Chloramphenicol), and Negative Control (Aquades). The results obtained two isolates of endophytic bacteria, namely isolates BEKC 1 with an inhibition zone of 9mm included in the medium category, and isolates BEKC 2 with an inhibition zone of 10mm included in the strong category. Analysis resultthat there was an effect of endophytic bacterial isolates from the leaves of the Chinese ketepeng plant (Cassia alata L) on the growth of Staphylococcus aureus bacteria. Then from the results of further tests using Duncan's test, it was found that each treatment, namely the negative control treatment was significantly different from BEKC 1, BEKC 2 and positive control, while there was no significant difference between BEKC 1, BEKC 2 and positive control. Keywords : Endophytic Bacteria, Chinese Ketepeng (Cassia alata L), Staphylococcus aureus